Two new species of Hydnophlebia (Meruliaceae, Polyporales) from China based on morphological and molecular evidence - Liu, Dong-Mei; Xu, Yun-Lin; Li, Yue; Liu, Wei-Hong; Ma, Hai-Xia; Huang, Man-Rong; He, Shuang-Hui (Phytotaxa, 2020)
Two new corticioid species, Hydnophlebia sinensis and H. subchrysorhiza, are described and illustrated from China. Hydnophlebia sinensis was collected from northern China (Beijing, Jilin and Shaanxi Provinces), while H. subchrysorhiza was collected from southern China (Hainan, Hunan and Yunnan Provinces). The two new species belong to the H. chrysorhiza species complex and are similar to each other with few morphological differences. However, they are phylogenetically independent in both the ITS-LSU tree of Meruliaceae and the ITS tree of Hydnophlebia. In the trees, H. sinensis was sister to H. sp., whilst H. subchrysorhiza was closely related to H. chrysorhiza. Our analyses show that we do not have H. chrysorhiza in China but possess two undescribed sibling species